Pengembangan Kurikulum Merdeka Belajar Pada Peningkatan Pemahaman Konsep Penyerbukan dengan Metode Demonstrasi di Kelas 4 SDN Sukorejo 2 Kota Blitar - Endang Puji Astuti (LP. Ma'arif Janggan Magetan, 2022)
The Independent Curriculum is a curriculum with diverse intra-curricular learning where the content will be optimized so that students have enough time to explore concepts and strengthen competencies. Teachers have the flexibility to choose various teaching tools so that learning can be adapted to the learning needs and interests of students. Especially in science learning about pollination, students are expected to not only get learning outcomes, but also get their own experience in learning. It can be seen that student learning outcomes so far are still lacking, namely from 12 students in grade 4 only 33% have achieved completeness. Such conditions require teachers to conduct research. The research used qualitatively on students in science learning. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The learning method used is demonstration, which is the presentation of lessons by demonstrating and showing students about a certain process, situation or object, either real or just an imitation.